Analysis of Carbon Emissions of Prefabricated Buildings from the Views of Energy Conservation and Emission Reduction - Ma, Weidong; Sun, Dacheng; Deng, Yongsheng; Meng, Xianyun; Li, Mi (Nature environment and pollution technology, 2021)
As a pillar industry with high energy consumption and low efficiency, the building industry of China has produced consistently high carbon emission levels in recent years. The important goals in the coordinated development of this industry include the large-scale development of green buildings, the use of energy technologies to reduce carbon emissions, and an effective reduction of carbon intensity. Prefabricated buildings have become popular in this industry due to their low energy consumption, emission, and pollution and environment-friendly nature. This paper examines those factors that influence the carbon emissions from the construction of prefabricated buildings across three phases, namely, production in plants, logistics transportation, and assembly construction, builds an evaluation index system for studying the carbon emissions in the materialization phase of prefabricated buildings, and employs the hierarchical fuzzy comprehensive evaluation method to construct an evaluation model. Results show that the overall energy consumption of prefabricated buildings is lower than that of traditional concrete pouring-type buildings. The hierarchical fuzzy comprehensive evaluation model is scientific and reasonable when used to measure the comprehensive benefits of carbon emissions from prefabricated buildings. By taking a project in Zhengzhou City, Henan Province as an example, the comprehensive evaluation results show that the carbon emissions of this project are at moderate levels. The carbon emissions from prefabricated buildings can be reduced by expanding the market scale of the building industry, adjusting its use of building materials, and setting up special funds for these buildings. The findings of this work provide a certain reference value for analysing the differences between prefabricated and traditional buildings in terms of their carbon emissions in the materialization phase, for evaluating how the carbon emissions of the former can be reduced, and for formulating and executing building emission reduction plans.